Trust and Human Challenge Vaccine Trials - Marshall, Benjamin D. (My University, 2022)
In a challenge trial, “healthy volunteers are intentionally exposed to pathogens in a controlled environment, in order to promote understanding of the pathogenesis, transmission, prevention and treatment of infectious diseases in humans.” (WHO 2021, Preface). Intentional infection is an uncomfortable concept, and as a result there is a widely held belief amongst research ethics scholars and commentators that a significant ethical concern with challenge trials is their potential to negatively impact the public’s trust in the institution of medical research (Eyal 2022, 4). However, the relationship between public trust and the ethics of conducting and assessing challenge trials is complex and existing literature on the subject does not sufficiently clarify it. This paper will begin by examining the ethical permissibility of challenge trials. Once these trials are shown to be ethically permissible under particular circumstances, I will explore how concerns about the way these trials allegedly exacerbate public mistrust largely result from ambiguities in the terms ‘public’ and ‘trust’. After both terms are defined, I will formulate my own account of how public trust should apply to a risk/benefit analysis for the purpose of trial design selection called the community engagement account, which argues that trial design selection policy should focus on demonstrating trustworthiness rather than garnering trust. Because demonstrating trustworthiness requires meeting a set of known expectations, this account identifies local, specific publics as those whose expectations should be of concern when discussing public trust and trial design selection. To examine the expectations of these publics, this account defends community engagement as the measure which should be used to acquire evidence of harmful public mistrust towards the institution of science that could potentially result from conducting a challenge trial.
EXAMINING THE RELATIONSHIP BETWEEN PUBLIC OPINION AND TRIAL DESIGN SELECTION
Keywords: Human Challenge Vaccine Trials; Public Trust